Frommer's EasyGuide to London - Cochran, Jason (FrommerMedia LLC, 2014)
Limited in pages, this EasyGuide is an exercise in creating easily-absorbed travel information. It emphasizes the authentic experiences in each destination: the most important attractions, the classic method of approaching a particular destination; the best choices for accommodations and meals; the best ways to maximize the enjoyment of your stay. Because it is "quick to read, light to carry", it is called an "EasyGuide", and reflects Arthur Frommer's lifetime of experience in presenting clear and concise travel advice. -- Publishers Description.